Strategi Pembelajaran Bahasa Arab dengan Menggunakan Model Pembelajaran Kooperatif Think-Pair-Share (Tps) Terhadap Peningkatan Kemampuan Membaca dan Menulis Bahasa Arab - Royyan Abdillah, Syafri; Puji Lestari, Annisa; Suparmanto, Suparmanto (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2023)
In learning Arabic, techniques or methods are needed that can support students so that they can understand the material conveyed by the teacher more quickly, especially in Indonesia, it is not easy for students to quickly understand Arabic because it is a foreign language. done is through the Think Pair Share learning model. This research uses classroom action research at MTS Nurul Haramain. This research lasts for two cycles. For data collection techniques in this research we’re using quantitative dan qualitative. The analytical method used is qualitative and quantitative research. The results showed that the application of the Think Pair Share method could improve students' Arabic reading and writing skills before the implementation of the Action. The average score obtained is 65% then in the first cycle the average score increases to 72%, and in the second cycle it increases to 95%. It means that at the end of the second cycle, the students have shown complete learning. The results of this study can be concluded that, using the Think Pair Share method can improve students' reading and writing skills. student learning outcomes in Arabic lessons increase in accordance with the KKM standards that have been determined by the school. The suggestions that the author can give can be a reference that the use of the Think Pair Share method can be used as an alternative for teachers and students in an effort to improve reading and writing Arabic skills, especially in fostering student learning activities to be more courageous and confident in expressing opinions. Think-Pair-Share (TPS) is a strategy to increase students' understanding in groups, where students with low levels of understanding will be combined with students who have high levels of understanding. This will help students who have low levels of understanding to be able to think more critically while learning through their group friends to be able to solve the problems given by the teacher. Because this TPS strategy requires students to be more active in class